Barrier function regulates epidermal DNA synthesis. - Proksch, E (1991)
We examined the possibility that the cutaneous permeability barrier regulates epidermal DNA synthesis in two acute and two chronic models of barrier perturbation. In animals treated topically with acetone, DNA synthesis is increased 102%, in tape-stripped animals 127%, in essential fatty acid deficient animals 50%, and in animals chronically treated with topical lovastatin 64%. This linkage between disturbances in barrier function and increased DNA synthesis is further supported by specific and correlative observations: (a) in these disparate models, artificial replacement of the barrier with a water-impermeable membrane inhibits the expected increase in DNA synthesis; (b) the extent of the burst in DNA synthesis is proportional to the degree of barrier abrogation; (c) the inhibition of DNA synthesis by membranes is directly related to the degree of permeability of these occlusive membranes, i.e., the more impermeable the greater the degree of inhibition; (d) topical treatment with lipids that restore barrier function corrects the increase in DNA synthesis; and (e) barrier abrogation with acetone produces an increase in epidermal DNA synthesis without altering bulk protein synthetic rates in contrast to events known to follow injury or cell replacement. Autoradiographic studies show that the increase in DNA synthesis after acetone treatment is limited to the epidermal basal layer. This constellation of findings strongly suggests that cutaneous barrier function is one factor that regulates epidermal DNA synthesis.